3D Spatiotemporal Mechanical Microenvironment A Hydrogel-Based Platform for Guiding Stem Cell Fate - Ma, Yufei (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.